Randomised controlled trial of sub-Tenon's block versus topical anaesthesia for cataract surgery: a comparison of patient satisfaction. Issue 3 (17th February 2005) - Rüschen, H; Celaschi, D; Bunce, C; Carr, C
Abstract : Background/aim: Sub-Tenon's block (STB) or topical anaesthesia alone (TOP) are popular techniques employed during cataract surgery. TOP is often preferred by healthcare providers because of financial or staffing reasons, despite existing evidence that pain during surgery is better controlled with STB. Pain is not the only consideration that determines patient preference for the anaesthesia technique. The authors decided to investigate the issue of patient satisfaction using the recently developed Iowa Satisfaction with Anesthesia Scale (ISAS). Method: In a randomised controlled pilot trial, 28 patients were enrolled to receive either STB with 3 ml of 2% lidocaine and hyaluronidase, or TOP with proxymetacaine 0.5% and amethocaine 1% (Tetracaine) eye drops. Postoperatively patients rated their satisfaction with anaesthesia care by filling in the self administered written questionnaire, the ISAS. Results: One patient in the TOP group dropped out of the study because of intolerable pain. Analysis of the questionnaire results with a two sample Wilcoxon rank sum test showed a significant difference in patient satisfaction (p<0.0085). The median satisfaction score was higher in the STB group 2.77 (interquartile range IQR 2.45 to 3), than in the TOP group 2.04 (IQR 1.54 to 2.5). Conclusion: In the setting of day case cataract surgery, patients report significantly higher satisfaction scores with STB than with TOP alone.